193 The role of the pi3k-alpha isoform in cardioprotection. (5th June 2017) - Rossello, Xavier; He, David; Riquelme, Jaime A; Davidson, Sean; Yellon, Derek M
Abstract : Introduction: Ischaemic preconditioning (IPC) limits infarct size (IS) through the activation of the PI3K-AKT signal cascade, known as the RISK pathway. The identification of the roles of individual PI3K isoforms should aid in the development of isoform-specific agents with improved cardioprotection. We aimed to elucidate the role of the PI3Kα isoform in cardioprotection. Methods: Male C57BL/6 mice were randomly allocated between groups in isolated perfused Langendorff experiments subjected to 35 min ischaemia and 2 hour reperfusion. Two distinct PI3Kα-isoform specific inhibitors (3μM of G326 and BYL719) were administered during the IPC protocol (4-cycles of 5 min ischaemia and 5 min reperfusion), or at reperfusion. PI3K activity was measured by Western blot analyses of AKT phosphorylation. Insulin was used as PI3Kα canonical activator. In addition, these studies were also undertaken using an in vivo mouse model. Finally, expression of PI3Kα protein levels was evaluated by Western blot in whole mouse heart and human atrial tissues (REC No. 00/0275), as well as in primary adult ventricular mouse cardiomyocytes and mouse cardiac endothelial cell (MCEC) line. Results: In the isolated Langendorff-perfused model, IPC reduced IS compared to control (49±4% vs 23±2%, p<0.001). Protection was not abolished using either G326 (26±3%) or BYL719 (25±3%) when administered during IPC (Figure 1A) despite the phosphorylation of AKT being inhibited. Interestingly, these same isoform inhibitors did block protection when given at reperfusion (G326 50±3%; BYL719 47±4%) (Figure 1B), in addition to blocking the AKT phosphorylation revealing a distinct role for the PI3Kα isoform during the early moments of reperfusion. Neither drug affected IS on its own. In support, the canonical PI3Kα activator, insulin, when given at reperfusion reduced myocardial IS compared to control (25±2 vs 55±4%, p<0.001) and this protection was abolished by G326 (Figure 2A). These experiments were confirmed in vivo when using the PI3Kα isoform inhibitor at reperfusion to block IPC protection (Figure 2B). On a tissue level, PI3Kα is expressed at the same level in mouse heart and human atrium. Interestingly, PI3Kα levels in MCEC were about 3-fold higher compared to adult ventricular mouse cardiomyocytes (p=0.047). Conclusions: Using a targeted pharmacological approach, we have demonstrated that the PI3KÎ± isoform is required during the reperfusion phase for protection conferred by IPC. The translational perspective is highlighted by the observation that human heart tissue expresses PI3KÎ±. This suggests that strategies specifically enhancing the ± isoform of PI3 kinase at reperfusion promotes tissue salvage and, as such, could provide an attractive target for clinical treatment of ischaemia-reperfusion injury.